Wave climate projections in the Western Black Sea using regional EURO-CORDEX wind forcing data - Nam Thanh Pham; Carolina Barnez Gramcianinov; Marcel Ricker; Joanna Staneva (Ocean Engineering, 2026)

A framework for morphological impact assessment of a small sandy beach under climate What-If Scenarios and Nature-based Solutions - Douglas Vieira da Silva; Wei Chen; Benjamin Jacob; Carolina Gramcianinov; Nam Thanh Pham; Marcel Ricker; Kelli Johnson; Johannes Pein; Joanna Staneva (Journal of Environmental Management, 2026)

The introduction of observation-based wave physics into the wind-wave model WAM: Wave assessments for a semi-enclosed basin - Marcel Ricker; Joshua Kousal; Heinz Günther; Arno Behrens; Joanna Staneva (Ocean Modelling, 2025)

Statistical spatial downscaling of significant wave height in a regional sea from the global ERA5 dataset - Bing Yuan; Marcel Ricker; Wei Chen; Benjamin Jacob; Nam Thanh Pham; Joanna Staneva (Ocean Engineering, 2025)

Analysis of terrestrial and riverine sources of plastic litter contributing to plastic pollution in the Western Black Sea using а lagrangian particle tracking model - Ivelina Zlateva; Marcel Ricker; Violeta Slabakova; Krasimira Slavova; Valentina Doncheva; Joanna Staneva; Emil Stanev; Ivan Popov; Carolina Gramcianinov; Violin Raykov (Marine Pollution Bulletin, 2024)

Correction to: Relative dispersion and relative diffusivities in an ocean-wave coupled model of the North Sea - Luciana Villa Castrillón; Marcel Ricker; Joanna Staneva; Jens Meyerjürgens; Thomas H. Badewien; Emil V. Stanev (Ocean Dynamics, 2024)

Relative dispersion and relative diffusivities in an ocean-wave coupled model of the North Sea - Luciana Villa Castrillón; Marcel Ricker; Joanna Staneva; Jens Meyerjürgens; Thomas H. Badewien; Emil V. Stanev (Ocean Dynamics, 2024)
The study analyzes the impact of various wave-induced processes on relative dispersion and diffusivities in the North Sea using OpenDrift, a Lagrangian particle-drift model driven by a fully coupled NEMO-WAM model. The coupled model parameterizations include sea state-dependent momentum flux, energy flux, and wave-induced mixing. The study demonstrates that Eulerian currents, influenced by the interaction between the ocean and wave models, significantly enhance particle transport. Experiments conducted using drifter clusters obtained during an RV Heincke excursion further confirm the impact of wind-wave coupling. The analysis includes a comparison of results from experiments with and without wave coupling. The impact of diffusion in the Lagrangian model on relative dispersion is investigated, with the conclusion that diffusion is essential for achieving precise simulations. Furthermore, the incorporation of wind-wave-driven mixing parameters, including sea state-dependent momentum flux, energy flux, and wave-induced mixing, into the hydrodynamic model leads to elevated levels of relative dispersion and diffusivity.

Sources, pathways, and abatement strategies of macroplastic pollution: an interdisciplinary approach for the southern North Sea - Jens Meyerjürgens; Marcel Ricker; Christian Aden; Michelle Albinus; Johna Barrelet; Holger Freund; Florian Hahner; Karsten A. Lettmann; Ingo Mose; Peter Schaal; Rosanna I. Schöneich-Argent; Emil V. Stanev; et al. (Frontiers in Marine Science, 2023)
The issue of marine plastic pollution has been extensively studied by various scientific disciplines in recent decades due to its global threat. However, owing to its complexity, it requires an interdisciplinary approach to develop effective management strategies. The multidisciplinary scientific approach presented here focuses on understanding the sources and pathways of macroplastic litter and developing abatement strategies in the southern North Sea region. Over 2.5 years, more than 63,400 biodegradable wooden drifters were deployed with the help of citizen science to study the sources, pathways, and accumulation areas of floating marine litter. Rivers act as sinks of most of the floating marine litter released within their waterways. Short-term field experiments were also conducted to analyse the hydrodynamic and atmospheric processes that govern the transport of floating litter particles at the sea surface. Numerical models were used to examine the transport of virtual litter particles in the entire North Sea and in coastal regions. It was found that there are no permanent accumulation areas in the North Sea, and the Skagerrak and fronts can increase the residence times of floating marine litter and favour sinking. Field surveys revealed that the majority of litter objects originate from fisheries and consumer waste. To develop effective abatement strategies, the key stakeholder landscape was analysed on a regional level. The interdisciplinary approach developed in this study highlights the importance of synergizing scientific resources from multiple disciplines for a better understanding of marine plastic pollution and the development of effective management strategies.

Monitoring and Forecasting the Ocean State and Biogeochemical Processes in the Black Sea: Recent Developments in the Copernicus Marine Service - Stefania A. Ciliberti; Marilaure Grégoire; Joanna Staneva; Atanas Palazov; Giovanni Coppini; Rita Lecci; Elisaveta Peneva; Marius Matreata; Veselka Marinova; Simona Masina; Nadia Pinardi; Eric Jansen; et al. (Journal of Marine Science and Engineering, 2021)
The Black Sea Monitoring and Forecasting Center (BS-MFC) is the European reference service for the provision of ocean analyses, forecasts, and reanalyses in the Black Sea basin. It is part of the Copernicus Marine Environment and Monitoring Service (CMEMS) and ensures a high level of efficiency in terms of operations, science, and technology for predictions and the monitoring of physical and biogeochemical processes in the Black Sea. The operational BS-MFC framework is based on state-of-the-art numerical models for hydrodynamics, biogeochemistry, and waves; analysis, forecast, and reanalysis are provided on a spatial grid with about 3 km of horizontal resolution that covers the whole Black Sea basin (the Azov Sea is not included). The scientific assessment of BS-MFC products is performed by implementing a product quality dashboard that provides pre-qualification and operational model skills according to GODAE/OceanPredict standards. Novel interfaces based on high-resolution models are part of the scientific development plan to ensure a strong connection with the nearest seas from a modelling point of view, in particular with the Mediterranean Sea. To improve forecasting skills, dedicated online coupled systems are being developed, which involve physics, biogeochemistry, and waves together with the atmosphere and, in the future, with ensemble forecasting methodologies and river-ocean interfaces.

Circulation of the European northwest shelf: a Lagrangian perspective - Marcel Ricker; Emil V. Stanev (Ocean Science, 2020)
The dynamics of the European northwest shelf (ENWS), the surrounding deep ocean, and the continental slope between them are analysed in a framework of numerical simulations using Lagrangian methods. Several sensitivity experiments are carried out in which (1) the tides are switched off, (2) the wind forcing is low-pass filtered, and (3) the wind forcing is switched off. To measure accumulation of neutrally buoyant particles, a quantity named the “normalised cumulative particle density (NCPD)” is introduced. Yearly averages of monthly results in the deep ocean show no permanent particle accumulation areas at the surface. On the shelf, elongated accumulation patterns persist in yearly averages, often occurring along the thermohaline fronts. In contrast, monthly accumulation patterns are highly variable in both regimes. Tides substantially affect the particle dynamics on the shelf and thus the positions of fronts. The contribution of wind variability to particle accumulation in specific regions is comparable to that of tides. The role of vertical velocities in the dynamics of Lagrangian particles is quantified for both the eddy-dominated deep ocean and for the shallow shelf. In the latter area, winds normal to coasts result in upwelling and downwelling, illustrating the importance of vertical dynamics in shelf seas. Clear patterns characterising the accumulation of Lagrangian particles are associated with the vertical circulations.

Interactions between barotropic tides and mesoscale processes in deep ocean and shelf regions - Emil Vassilev Stanev; Marcel Ricker (Ocean Dynamics, 2020)
The interactions between barotropic tides and mesoscale processes were studied using the results of a numerical model in which tidal forcing was turned on and off. The research area covered part of the East Atlantic Ocean, a steep continental slope, and the European Northwest Shelf. Tides affected the baroclinic fields at much smaller spatial scales than the barotropic tidal scales. Changes in the horizontal patterns of the M 2 and M 4 tidal constituents provided information about the two-way interactions between barotropic tides and mesoscale processes. The interaction between the atmosphere and ocean measured by the work done by wind was also affected by the barotropic tidal forcing. Tidal forcing intensified the transient processes and resulted in a substantial transformation of the wave number spectra in the transition areas from the deep ocean to the shelf. Tides flattened the sea-surface height spectra down to ~ k −2.5 power law, thus reflecting the large contribution of the processes in the high-frequency range compared to quasi-geostrophic motion. The spectra along sections parallel or normal to the continental slope differ from each other, which indicates that mesoscale turbulence was not isotropic. An analysis of the vorticity spectra showed that the flattening was mostly due to internal tides. Compared with the deep ocean, no substantial scale selectivity was observed on the shelf area. Particle tracking showed that the lengths of the Lagrangian trajectories increased by approximately 40% if the barotropic tidal forcing was activated, which contributed to changed mixing properties. The ratio between the horizontal and vertical scales of motion varied regionally depending on whether barotropic tidal forcing was included. The overall conclusion is that the barotropic tides affect substantially the diapycnal mixing.

The Fate of Marine Litter in Semi-Enclosed Seas: A Case Study of the Black Sea - Emil V. Stanev; Marcel Ricker (Frontiers in Marine Science, 2019)